Creación de una tienda de alquiler de vestidos de fiestas para damas - Borja Heredia, Alejandra Patricia (2019)
The need to dress well and fashion has been, is and always will be an important need in women, much more so if women are currently actively participating in the organization occupying different dignities. This requires that there is always the imperative need to look elegant in every social event they attend. Through this project a entrepreneurship initiative is detailed, in which an offer for the rental of gala dresses for women is established, where they can find aspects such as exclusivity in clothing and the variety of designs and models, supporting This way they can better meet their clothing needs and save money, since they will not have to buy the garment